Don’t stop walking: the in-home rehabilitation program for peripheral artery disease patients during the COVID-19 pandemic - Lamberti, Nicola; Straudi, Sofia; Manfredini, Roberto; De Giorgi, Alfredo; Gasbarro, Vincenzo; Zamboni, Paolo; Manfredini, Fabio (Internal and emergency medicine, 2021)
We studied the outcomes of peripheral artery disease (PAD) patients enrolled in a structured in-home walking program right before the lockdown due to the SARS-CoV-2 epidemic emergency, to determine whether this intervention ensured the maintenance of mobility even in the case of movement restrictions. We selectively studied 83 patients (age 72 ± 11, males n = 65) enrolled in the program within 9-month before the lockdown. The usual intervention was based on two daily 8-min sessions of slow intermittent in-home walking prescribed in circa-monthly hospital visits. During the lockdown, the program was updated by phone. Six-minute (6MWD) and pain-free walking distance (PFWD) were measured pre- and post-lockdown as well as body weight (BW), blood pressure (BP), and ankle-brachial index (ABI). Sixty-six patients were measured 117 ± 23 days after their previous visit. A safe, pain-free execution of the prescribed sessions was reported (median distance: 74 km). Overall, the 6MWD was stable, while PFWD improved ( p < 0.001). The improvement was not related to age/gender, comorbidities, type of home but to the time of enrollment before lockdown. The new-entry subjects (≤ 3 months; n = 35) obtained significant improvements post-lockdown for 6MWD and PFWD, while those previously enrolled (> 3 months; n = 31) were stable. Decreased BW with stable BP and ABI values were also recorded, with better outcomes for new-entry subjects. In PAD patients, a structured walking program performed inside home and purposely guided by phone was adhered to by patients and favored mobility and risk factor control during the COVID-19 pandemic, regardless of walking ability, type of home and external conditions.